A Case of Ischemic Stroke in a Patient with Middle Cerebral Artery Stenosis and Iron Deficiency Anemia - Parvu, T.; Coclitu, C.; Rusu, O.; Ciobotaru, A.; Mergeani, A.; Bajenaru, O.; Antochi, F. A. (Journal of Hematology Research, 2016)
Recent studies showed that iron deficiency anemia was correlated with ischemic stroke in patients with carotid artery stenosis. It was also identified as the culprit of ischemic stroke in patients without any acknowledged risk factors for stroke. We presented a clinical case that highlights the importance of the management of anemia as etiologic factor of ischemic stroke, both as primary and secondary prevention.